Adult bilinguals outperform monolinguals in theory of mind. Issue 11 (November 2021) - Navarro, Ester; Conway, Andrew RA
Theory of mind (ToM) is an essential ability for social competence and communication, and it is necessary for understanding behaviours that differ from our own. Research on bilingual children has reported that 3- and 4-year-old bilinguals outperform monolinguals in ToM tasks. Research suggests that adult bilinguals also might outperform monolinguals; nevertheless, this effect has yet to be established. Here, we tested bilingual and monolingual adults on the director task. Results showed that bilingual adults outperformed monolinguals in response to perspective-dependent trials of the director task, but not in response to control trials. This suggests that bilingualism is associated with individuals' ability to take into account the perspective of another person. In addition, the number of cultures that participants were exposed to, regardless of whether the participant was bilingual or not, was also associated with ToM performance. Overall, the findings suggest that linguistic and cultural experience have an impact on ToM.